The Prayer to Pan of Plato's Phaedrus (279b8–c3): An Exhortation to Exercise the Philosophical Virtue. Issue 1 (1st January 2018) - Lavilla de Lera, Jonathan
Abstract : The current article offers a new reading of Socrates' prayer to Pan in Plato's Phaedrus . By means of a comprehensive approach, the paper shows that the prayer not only gathers together the most relevant topics dealt with during the conversation but it also exhorts us to engage in the way of life depicted by Socrates' character, namely that of philosophy, which can be clearly distinguished from that of traditional rhetoric. To this extent, eros and logos, two elements closely related to Pan, show themselves to be of primary relevance. Besides these issues, we discuss the puzzling nature of the prayer, defending the idea that it was authored with the same writing method as the full dialogue. Socrates' psychagogic attempt with Phaedrus is analogous to Plato's didactic effort to engage the reader in philosophy: instead of supplying a straight message which must be learnt by heart by Phaedrus or the reader, both Socrates and Plato offer friendly logoi intended to promote active research in the receivers.